2004
DOI: 10.1080/02652030410001713906
|View full text |Cite
|
Sign up to set email alerts
|

Presence and concentrations of theFusarium-related mycotoxins beauvericin, enniatins and moniliformin in finnish grain samples

Abstract: Fusarium mycotoxins beauvericin, enniatins (A, A1, B, B1) and moniliformin were analysed in 38 Finnish grain samples (14 wheat, 22 barley, one rye, one oats) harvested in 2001-02. The contaminating Fusarium species were identified with the primer-specific polymerase chain reaction as well as with morphological studies. All the studied mycotoxins were found in the samples. Enniatins B and B1 were detected in all samples, and enniatin A, enniatin A1, beauvericin and moniliformin in 74, 95, 95 and 74% of the samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
136
2
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(161 citation statements)
references
References 39 publications
16
136
2
2
Order By: Relevance
“…On the other hand, although the ENNs, AUR, MON, EQU, BIK, BEA, fumonisins, FA, 3-ADON, NIV, ZEA, DEC, BUT, TENT, AOH and AME have been detected at lower levels than the DON, DON-3G and CULM, the presence of some of them have been reported for the first time in the current study in naturally infected winter wheat from Southern Europe. The levels of MON, BEA and NIV are comparable to those reported by Jestoi et al (2004), Uhlig et al (2007Uhlig et al ( , 2013 and Lindblad et al (2013). ENNs have been detected at comparable or slightly lower levels, depending on which growing season was considered in the previously cited studies, while AUR, ZEA, EQU, BUT and 3-ADON are present at lower values than those found by Uhlig et al (2013).…”
Section: Discussionsupporting
confidence: 67%
“…On the other hand, although the ENNs, AUR, MON, EQU, BIK, BEA, fumonisins, FA, 3-ADON, NIV, ZEA, DEC, BUT, TENT, AOH and AME have been detected at lower levels than the DON, DON-3G and CULM, the presence of some of them have been reported for the first time in the current study in naturally infected winter wheat from Southern Europe. The levels of MON, BEA and NIV are comparable to those reported by Jestoi et al (2004), Uhlig et al (2007Uhlig et al ( , 2013 and Lindblad et al (2013). ENNs have been detected at comparable or slightly lower levels, depending on which growing season was considered in the previously cited studies, while AUR, ZEA, EQU, BUT and 3-ADON are present at lower values than those found by Uhlig et al (2013).…”
Section: Discussionsupporting
confidence: 67%
“…For a given mycotoxin, the amount produced and its physical-chemical properties may be used for a first assessment of their environmental emission potential. Concentrations of enniatins in cereals can very well be in the order of milligrams per kilograms (27,28), i.e., similar to those of deoxynivalenol. Among all mycotoxins, moniliformin might dominate in runoff and drainage water because it is produced in high amounts (29) and because of its anionic and thus readily water-soluble speciation.…”
Section: ) (B) Deoxynivalenol Concentrations (Ng/l) (C) Zearalenonementioning
confidence: 99%
“…The fungi that produce moniliformin also produce other mycotoxins, such as fumonisins, beauvericin, fusaproliferin, fusarins, trichothecene, and zearalenone [82][83][84][85][86][87][88][89], which are generally found in mixtures with moniliformin [83][84][85][86][87][88].…”
Section: Moniliforminmentioning
confidence: 99%